Pengaruh Jenis Pupuk Kandang dan Dosis Pupuk Organik Cair dari Limbah Batang Pisang terhadap Sifat Kimia Tanah dan Hasil Bayam Hijau (Amaranthus hybridus L.) - BARUS, YEMIMA INDRI YANI BR; SONIARI, NI NENGAH; ARTHAGAMA, I DEWA MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.3, Juli 2022, 2022)
Effect of Manure Type and Dosage of Liquid Organic Fertilizer from Banana Stem Waste on Soil Chemical Properties and Yield of Green Spinach ( Amaranthus hybridus L . ) Organic fertilizers can improve the physical, chemical and biological properties of soil because they contain macro and micro nutrients that are useful for plants. This aims of the study to determine the interaction and effect of type of manure and dosage of Liquid Organic Fertilizer (POC) on soil chemical properties and yield of green spinach which was carried out from July 2021 to November 2021 in Sukadame Village, Tigapanah District, Karo Regency, North Sumatra Province. Banana tree trunks are useful for fertilizing plants, and contain very high phosphorus nutrients. The experimental design used in this study was a completely randomized design (CRD) with a factorial pattern consisting of 2 factors, namely the type of manure and the dose of liquid organic fertilizer with, A 0 : no manure, A 1 : goat manure, A 2 : chicken manure, A 3 : cow manure, while the doses of liquid organic fertilizer are B 0 : without liquid organic fertilizer, B 1 : 0.75 liters of liquid organic fertilizer, B 2 : 1.50 liters of liquid organic fertilizer and B 3 : 2.25 liters of liquid organic fertilizer and repeated 3 times so that it becomes 48 units of experimental pot. The interaction between the type of manure and the dose of liquid organic fertilizer had a very significant effect on organic C, available K and available P content. The best manure is chicken manure with soil pH (6.40), soil moisture content (16.45%) and total N content (0.66%). The best change in soil chemical properties was treatment with a dose of liquid organic fertilizer at a dose of 0.75 liters, with soil pH (6.40), soil moisture content (17.29%) and total N content (0.67%), and for influence. the yield is at a dose of 0.75 liters of liquid organic fertilizer with a fresh plant weight of 10.83g.